From Experience To Loyalty: Co-Creation In Sport Tourism Events - Nesya Nandini; Pangestuti, Edriana; Abdillah, Yusri (Journal of Indonesian Tourism and Development Studies, 2025)
This study explores how co-creation experience and event service quality influence visitor satisfaction and revisit intention in the context of sport tourism events. Using the theoretical lens of the Stimulus-Organism-Response (SOR) model and Service-Dominant Logic (SDL), the research focuses on participants of the Colour Fun Run JTP Colour FunFest 2024 held in Batu City, Indonesia. Data were collected via a structured questionnaire from 130 participants and analyzed using PLS-SEM. The findings reveal that both co-creation experience and event service quality significantly affect satisfaction, which in turn influences revisit intention. The study highlights the critical role of participatory event design and service excellence in fostering repeat visitation in sport tourism.